2016
DOI: 10.1111/jcpt.12346
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in the management of glioblastoma in a French University Hospital and associated direct costs

Abstract: This is the first study to report on changes in the management of GBM in real-life practice. The ten-year study indicates an improvement in overall survival but also an increase in total cost of care. The data should be useful for informing the care of GBM patients in settings similar to ours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Together, these trials indicate that improved resection directly extends survival and enhances the treatment effect of radical chemo-radiotherapy. Both 5-ALA guided surgery and temozolomide based chemo-radiotherapy are being used increasingly in modern practice with a demonstrated increase in overall survival [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together, these trials indicate that improved resection directly extends survival and enhances the treatment effect of radical chemo-radiotherapy. Both 5-ALA guided surgery and temozolomide based chemo-radiotherapy are being used increasingly in modern practice with a demonstrated increase in overall survival [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous neurosurgical studies highlight the benefits of wide-field fluorescence-guided glial tumor resection, mainly to increase the GTR rate and progression-free survival ( 2 , 111 , 188 ). Some studies even showed increased overall survival ( 189 ).…”
Section: Instrumentation For Fluorescence-guided Resectionmentioning
confidence: 99%
“…Despite the rise in studies on 5-ALA-guided surgery, cost-effectiveness analyses on this adjunct are limited. 2,20 We conducted the first systematic review on the cost-effectiveness of 5-ALA. Three primary studies were analyzed; all of which examined the perspective of a national healthcare system. Overall, while there is a paucity of high-quality data pertaining to the cost-effectiveness of 5-ALA, the currently available data suggest this adjunct is cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Discounting rates of 0%, 3%, 5%, and 7% were applied, with ICER per LY gained ranging from €5,963/C$8,885 to €7,473/C 17 Esteves et al 1 Henaine et al 20 Mean total cost of surgery iii. Current trends in the management of GBM in a French University Hospital and associated direct costs.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation